Rancangan Kemasan Buah Alpukat (Persea Americana Mill) Menggunakan Serbuk Gergaji Kayu - Ferdad Miza Taufiq; Tamrin Tamrin; Winda Rahmawati; Warji Warji (Jurnal Agricultural Biosystem Engineering, 2022)
This study aim to design avocado packaging using wood sawdust with an organic adhesive composition that is suitable and can reduce the damage of avocados during transportation and distribution. The ingredients used were round green butter avocado varieties, 8 mesh wood sawdust and 50 mm size, tapioca adhesive, molasses, and PVAc. While the tools used are transportation simulation tables, presses, molding, UTM, and rheo meters. The results showed the prototype of the individual packaging has dimension of (8,5 x 8,5 x 12) cm with the diameter of the hole 7,5 cm and the volume of the prototype of 646 cm3. From the calculation of packaging dimensions (40.5 x 24.5 x 12) cm with thickness packaging 1 cm and the distance between the holes 0,5 cm, where the fruit used had a diameter of ± 7.22 cm and a height of ± 9.015 cm. The amount of fruit used in one package is 15 avocados. The best packaging prototype (A2P1) using 50 mm wood sawdust with tapioca adhesive has the greatest compressive strength of 1,048 Pa so that the packaging can be used for 50 stacks equal to 6 m. This packaging is able to protect and help maintain the quality of avocado products during distribution with transportation mileage of 215.04 km with the lowest level of mechanical damage which is 16.66%.